(untitled) (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to determine the effect of the implementation of the zoning policy on students’ learning motivation at SD Negeri 2 Sopai. This research was conducted at SD Negeri 2 Sopai Toraja Utara. The data collection techniques used in this study were questionnaires, interviews, and observation documentation. The data analysis method used is a simple linear regression test method, validity test, reliability test and product moment correlation test to determine the education zoning policy variable has a positive and significant effect on the learning motivation of SD Negeri Sopai students. Based on the results of the research that has been done, there is a positive influence on the learning motivation of SD Negeri 2 Sopai students and the implementation of the education zoning policy has a strong and significant correlation to the development of student motivation in SD Negeri 2 Sopai. Keywords: Policy Implementation, School Zoning, Learning Motivation